Varroa Mite, Varroa destructor Anderson and Trueman (Arachnida: Acari:Varroidae) - James D. Ellis; Catherine M. Zettel Nalen (EDIS)
EENY-473, an 8-page illustrated fact sheet by James D. Ellis and C. M. Zettel Nalen, is part of the Featured Creatures collection. It describes this devastating pest of Western honey bees — distribution, description, life cycle, economic importance, detection, and management. Includes references. Published by the UF Department of Entomology and Nematology, June 2010.